STP Analysis (Segmenting, Targeting and Positioning) of Private Vocational Secondary Level Educational Institutions: A Study on Business and Technology High School in Bekasi - Nursetiani, Andini; Safaria, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the segmentation, targeting, and positioning (STP) strategies applied by SMK Bisnis dan Teknologi Bekasi, a vocational high school. Through a case study approach, this research reveals how this private vocational institution employs the STP concept in their marketing and promotional efforts. Segmentation is carried out in various dimensions, including geographical and demographic segmentation. The results of the STP analysis demonstrate that the school identifies prospective student segments based on age, educational background, and career aspirations. The position taken by the school is that of an educational provider offering the capability to immediately enter the workforce upon graduation, with study programs aligned to industry needs. In terms of marketing, SMK Bisnis dan Teknologi Bekasi employs measures through social media and digital marketing to reach their targeted segments. Within this context, the study provides insights into how the STP concept can be applied in an educational context and how appropriate marketing strategies can aid educational institutions in achieving their goals